The formation of the thumb requires direct modulation of Gli3 transcription by Hoxa13 - Bastida, Maria Félix; Pérez-Gómez, Rocío; Trofka, Anna; Zhu, Jianjian; Rada-Iglesias, Alvaro; Sheth, Rushikesh; Stadler, H. Scott; Mackem, Susan; Ros, Marian A. (Proceedings of the National Academy of Sciences - PNAS, 2020)
In the tetrapod limb, the digits (fingers or toes) are the elements most subject to morphological diversification in response to functional adaptations. However, despite their functional importance, the mechanisms controlling digit morphology remain poorly understood. Here we have focused on understanding the special morphology of the thumb (digit 1), the acquisition of which was an important adaptation of the human hand. To this end, we have studied the limbs of the Hoxa13 mouse mutant that specifically fail to form digit 1. We show that, consistent with the role of Hoxa13 in Hoxd transcriptional regulation, the expression of Hoxd13 in Hoxa13 mutant limbs does not extend into the presumptive digit 1 territory, which is therefore devoid of distal Hox transcripts, a circumstance that can explain its agenesis. The loss of Hoxd13 expression, exclusively in digit 1 territory, correlates with increased Gli3 repressor activity, a Hoxd negative regulator, resulting from increased Gli3 transcription that, in turn, is due to the release from the negative modulation exerted by Hox13 paralogs on Gli3 regulatory sequences. Our results indicate that Hoxa13 acts hierarchically to initiate the formation of digit 1 by reducing Gli3 transcription and by enabling expansion of the 5′Hoxd second expression phase, thereby establishing anterior–posterior asymmetry in the handplate. Our work uncovers a mutual antagonism between Gli3 and Hox13 paralogs that has important implications for Hox and Gli3 gene regulation in the context of development and evolution.